Situation report on Nepal’s agrifood systems: April 2024 - Palikhe, A.; Adhikari, M.; Maharjan, N.K.; Gupta, S.; Kumar, A.; Minot, Nicholas; Koirala, Pankaj; Krupnik, Timothy J. (CSISA, 2024)
In March 2024, Nepal witnessed moderate inflation. Overall consumer inflation reached 4 .8 percenton a year-on-year basis, while food and beverage inflation stood at 5.9 percent. The year-on-year wage rate index for agricultural labor showed a significant increase, however, agricultural labor wages remained constant over February-March. Remittances increased with the rise in labor permits for foreign employment. Staple foods such as rice, wheat flour, lentils, and black beans remained stable in February 2024 compared to the previous month. Additionally, the prices of vegetables such as tomatoes, potatoes, and carrots decreased over the same period. Similarly, the prices of proteinrich sources like milk, eggs, meat, and fish moderately decreased in February compared to the earlier month, while the price of edible oil continued to fall during this period.